2021
DOI: 10.1186/s12889-021-10856-z
|View full text |Cite
|
Sign up to set email alerts
|

Trust in health information sources and its associations with COVID-19 disruptions to social relationships and health services among people living with HIV

Abstract: Background SARS-CoV-2 infection (COVID-19) is potentially severe for individuals with compromised immune systems, including people living with HIV. Along with the direct health threats of COVID-19, there are disruptions to social relationships and health services resulting from mitigation efforts instituted by public health authorities. This study examined the relationship between trust in the government and trust in COVID-19 health information from the US CDC, state health departments, and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Containment measures of COVID-19 taken in Ethiopia had a significant contribution to halting the spread of COVID-19 in Ethiopia; however, they had their own implications on HIV care and treatment services as the response from the patients with HIV as indicated. Transport disruption, partial lockdown that impaired mobility, and income reduction were significant factors in missing health care visits, which was in agreement with previous studies conducted in Ethiopia (13,42), and elsewhere in the world (43)(44)(45)(46)(47)(48)(49)(50) that the COVID-19 containment measure had a significant impact on patients' access to healthcare facilities. Undue expenses related to protective equipment, including face masks and sanitizers, were a burden for the people living with HIV.…”
Section: Discussionsupporting
confidence: 90%
“…Containment measures of COVID-19 taken in Ethiopia had a significant contribution to halting the spread of COVID-19 in Ethiopia; however, they had their own implications on HIV care and treatment services as the response from the patients with HIV as indicated. Transport disruption, partial lockdown that impaired mobility, and income reduction were significant factors in missing health care visits, which was in agreement with previous studies conducted in Ethiopia (13,42), and elsewhere in the world (43)(44)(45)(46)(47)(48)(49)(50) that the COVID-19 containment measure had a significant impact on patients' access to healthcare facilities. Undue expenses related to protective equipment, including face masks and sanitizers, were a burden for the people living with HIV.…”
Section: Discussionsupporting
confidence: 90%
“…However, it may start with listening to individuals’ concerns and reassuring them of professional work, providing accurate information, and serving selflessly. 20 , 33 , 43 , 44 This finding is similar to previous studies 35–37 although one study reported contrary findings. 34 …”
Section: Discussionsupporting
confidence: 90%
“… 27 , 30–32 Re-building or improving generalized trust may be needed in the case of poor COVID-19 vaccine uptake through honest and sincere conversation between officials and individuals (where individuals’ views are considered) although that may take a considerable time to accomplish. 24 , 25 , 43 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…Low trust in government advice and recommendations due to its perceived handling of the pandemic and changing COVID-19 messaging was identified as a potential barrier to vaccine acceptability and uptake in our study and others [21] [22]. The link between mistrust in a COVID-19 vaccine and mistrust in government was found to be more pronounced among some minority ethnic participants in a small qualitative study amongst UK HCPs, particularly Black African, Black Caribbean and other Black groups[23].…”
Section: Discussionmentioning
confidence: 72%